Detention Properties of Subsurface Stormwater Modules Under Tropical Climate - Bong, C. H. J.; Lim, L. L. P.; Ng, C. K.; Chai, S. L. (International Journal of Integrated Engineering, 2023)
Subsurface stormwater module is one of the components of a sustainable drainage system. However, the performance of subsurface stormwater module as on-site detention under tropical climate like Malaysia has not been extensively studied in the literature. The current study involves on-site installation of pilot scale subsurface stormwater modules exposed to tropical climate to simulate real conditions to evaluate the detention performance. Rainfall together with the changes in water level and volume of water detained in the installation were observed for six months between April 2021 to October 2021. The subsurface stormwater module used in the current study has a porosity of 94%. It was found that the subsurface stormwater module setup was able to detain between 35.2% to 95.6% of the rainfall volume generated from total rainfall between 11.1 mm to 56.8 mm. The findings can be used as design consideration for using subsurface stormwater module under tropical climate.